Perbedaan perawatan tali pusat menggunakan kassa kering steril dan kassa lembab terhadap lamanya puput di RS TNI-AD Guntur Garut - Iin Patimah; Yuliana Dewi (STIKes Karsa Husada Garut, 2014)
Umbilical cordcare is the most important to avoidthe occurrence ofinfectionsin newborns. Umbilical cord care is stil lallowed as long as done by rubbing alcohol or providon iodine. The general objective of this study was to determine the difference Umbilical Cord Care Using Dry gauze and Moist Gauze for placenta releasing on new bornsin Hospital Guntur Garut in 2013. This research used the quasi experiment design Intake Group Comparison test, the sample used was 44 respondents, divided into 2 treatment groups using a dry sterile gauze and gauzemoist. The results of the study by using a dry sterile gauze, the average length of cord puput 4 days and 7 days moist gauze. There are significant differences in for placenta releasing on baby browusing sterile gauze and moist gauze (p-value = 0.0001), or there is a significant effect of treatment on the duration of for placenta releasing on newborns in the Hospital Army Guntur Garut in 2013. To care further recommended the umbilical cord using a dry sterile gauze.